2019
DOI: 10.29356/jmcs.v53i1.1012
|View full text |Cite
|
Sign up to set email alerts
|

Isocordoin Derivatives From the Root Extract of Lonchocarpus xuul

Abstract: Two natural isocordoin derivatives, dihydroisocordoin (1) and flemistrictin B (2), were isolated from the root extract of Lonchocarpus xuul. Both metabolites were identified on the basis of their spectroscopic data and by comparing them with those reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Psoralea corylifolia , a known traditional medicine for Indians and Chinese, has also yielded bavachromanol, a novel natural chalcone [ 26 ]. Dihydrochalcone, dihydroisocordon, and flemistrictin B have been isolated from Lonchocarpus xuul root extract [ 27 ]. In a comprehensive review by Wang et al (2020), about 42 chalcones isolated from licorice have been reported [ 28 ].…”
Section: Naturally Occurring Chalconesmentioning
confidence: 99%
“…Psoralea corylifolia , a known traditional medicine for Indians and Chinese, has also yielded bavachromanol, a novel natural chalcone [ 26 ]. Dihydrochalcone, dihydroisocordon, and flemistrictin B have been isolated from Lonchocarpus xuul root extract [ 27 ]. In a comprehensive review by Wang et al (2020), about 42 chalcones isolated from licorice have been reported [ 28 ].…”
Section: Naturally Occurring Chalconesmentioning
confidence: 99%
“…(Sapindaceae), an endemic plant commonly used in Yucatecan traditional medicine to treat infections, showed marked in vitro and in vivo activities against Trypanosoma cruzi. 22 The bioassay-guided purification of the crude extract yielded a bioactive fraction containing a mixture of the sesquiterpene βcaryophyllene oxide (26) and the triterpene lupenone (28), both of which were not active when tested separately. 39 Recently, the synergistic effect of a 1:4 mixture of 26 and 28 was confirmed when tested against epimastigote forms of T. cruzi.…”
Section: ■ Screening the Mayan Pharmacopeiamentioning
confidence: 99%
“…In the initial investigation of the phytochemical components from Lonchocarpus spp., the chromatographic fractionation of the hexane-soluble portion of the leaf methanolic extracts of Lonchocarpus xuul Lundell and L. yucatanensis Pittier led to the isolation of the new chalcone 4,2′-dimethoxy-6′-hydroxylonchocarpin ( 1 ) . In addition, purification of the root extract of L. xuul yielded two isocordoin derivatives identified as dihydroisocordoin ( 2 ) and flemistrictin B ( 3 ); a third chalcone, having the same molecular formula and similar spectroscopic data to those of 3 , was also isolated from the root extract of L. xuul and identified as epi -flemistrictin B ( 4 ). The configuration at the C-2″ position of the epimeric chalcones 3 and 4 was established on the basis of theoretical calculations of the H-2″ chemical shift for each of the epimeric structures; the results showed that the H-2″ in the alpha orientation appears at a significantly higher field than that in the beta orientation …”
Section: Natural Products From the Yucatan Floramentioning
confidence: 99%